(untitled) (Journal of the Association for the Study of Australian Literature, 2023)
This paper emerges from a panel discussion at the ‘Texts and Their Limits’ conference (2021) between four scholars in the field of Australian regional literary history to consider its current concerns, practices and relationship to the frameworks of Australian literary studies. The panel flagged a renewal of regional literary scholarship in Australia through exploration of the panelists’ own projects and collaborations in regional and rural Victorian and Western Australian communities. Drawing on their reflections on the doing of regional literary history, the conversation canvassed the distinct qualities of contemporary regional Australian literary scholarship; the role of place, situated practice and community engagement in this field; and the implications for the regional literary studies of the always unsettled boundaries and status of the ‘region’ in Australian life. Following the original panel event, this paper discusses questions such as: what is regional literary history, where is it going, and what are limits?